Designing Vocabulary Materials Through Digital Comic for The Seventh Graders - Sita Ariyani, Febi; Hary Setyawan , Agustinus ((JELE) Journal Of English Language and Education, 2024)
Many students had problem in comprehending English vocabularies. This study aimed to find out whether the materials designed through a media namely digital comic in teaching vocabularies can increase the seventh graders comprehension of English vocabularies. The study involved 32 students of class VII. The pre-test and post-test were used to analyze the students’ progress. It was shown that the average score found in pre-test was 63,7, and the average score in post-test was 89,07. It means that the post-test score was higher than pre-test. In conclusion, the finding of the study showed that digital comic improves the seventh graders comprehension of English vocabularies. There for digital comic can be used as alternative media in teaching vocabulary in order to enrich the students’ vocabulary